FORMATION OF INDEPENDENCE OF CHILDREN OF SENIOR PRESCHOOL AGE BY MEANS OF PROBLEM TASKS - Pantiuk, Tetiana; Nevmerzhytska, Olena; Horodyska, Violeta; Sharan, Oleksandra; Bereza, Svitlana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Considering the current situation in the educational space of Ukraine, the teacher should cultivate in the younger generation the ability to analyze, think critically, find solutions to problems, develop a personality capable of taking responsibility for their own actions and deeds. In this context, the problem of independence education is relevant, significant both in theoretical and practical aspects. We associate perspective ways of research with the study of the implementation of modern scientific approaches to the transformation of the pedagogical process, increasing attention to the personality of the child as an agent of cognitive activity, providing him with freedom of choice of activities and forms of participation in it, democratization of the educational process on the basis of cooperation between teachers and pupils, differentiation of education and training, development of flexible pedagogical technologies that best meet the needs and capabilities of pupils, in their independent mastering of various aspects of life. In this context, problem tasks that put the child in a situation where he/she is encouraged to use various methods of mental activity (comparison, analysis, synthesis, classification) are of undeniable value. This activates independence, the ability to find ways to solve problems, draw conclusions and generalize. Therefore, the aim of the study is the search for effective ways to form independence in children of senior preschool age. Studying the formation of independence as a basic personal quality in children of senior preschool age, we were guided by the fact that the independence of children of this age group is best manifested in new unfamiliar situations. By solving them, children can demonstrate independence of thought, originality of ways to solve the problem. In the light of this, we took into account the children's interest in independent actions in the conditions of choosing between the new and the familiar; independence and autonomy of actions in relation to the adult; ways of solving the problem; the result of the activity. As a result of the experimental study, we found that a significant number of children in the experimental group do not realize the possibilities of independence and do not reach the optimal level of its formation. The search for ways to solve this problem made it possible to identify effective means of forming independence in children of senior preschool age, among which a special place is occupied by problem solving tasks. They put children in the conditions of practical search for a solution to the problem, which pushes them to search independently, awakens the child's opinion, forms non-standard thinking. Such tasks encourage children to express their original ideas, to analyze problematic and ambiguous situations, to establish cause-and-effect relationships, to think over the situation, to build hypotheses, which also stimulates independence of thinking, flexibility of mind, develops creative abilities of the child. Thus, problem-bases tasks effectively influence the development of preschoolers' independence as an integral quality of personality.